Pelatihan sport massage berbasis android untuk mengatasi delayed onset muscle soreness bagi pelatih olahraga beladiri tarung derajat - Sari Mariati; Desi Purnama Sari; Weni Sasmitha; Anisa Sholiha Mia; Yogi Arnaldo; Suci Nanda Sari (Lentera Negeri, 2024)
Delayed Onset Muscle Soreness (DOMS) is a symptom often experienced by sportsmen in the form of uncomfortable pain in the muscles when just starting the exercise experienced the next day. DOMS can be overcome with Sport Massage treatment. The technique of doing Sport Massage for handling DOMS can be downloaded freely through the Android Application. The purpose of this service is for Android-based Sport Massage training to overcome Delayed Onset Muscle Soreness (DOMS) to the Main Trainers of Tarung Derajat martial arts sports in West Sumatra. Measuring the level of achievement of socialization as well as Android-based Sport Massage training to overcome Delayed Onset Muscle Soreness (DOMS) is by practical evaluation through direct observation. The stages carried out in this training are 1) discussion, 2) training and 3) evaluation. Evaluation. The results of this activity provide an increase in knowledge and understanding of Tarung Derajat martial arts coaches on the importance of Sport Massage and its application in Tarung Derajat martial arts and the coaches have been able to evaluate athletes who have practiced the given Sport Massage.